2019
DOI: 10.1002/jcop.22168
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination, John Henryism coping, and behavioral health conditions among predominantly poor, urban African Americans: Implications for community‐level opioid problems and mental health services

Abstract: The current study examined the relationship between John Henryism Active Coping (JHAC), experiences of racial discrimination, and behavioral health outcomes in a community sample of 319 Black adults. Assessments included primary health care screenings as well as self-reported survey questions to assess JHAC, experiences of discrimination, and self-reported behavioral health. Logistic regressions model adjusted for control variables, found a significant relationship between JHAC and having an opioid problem (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Studies utilizing total scores on the JHAC scale have reported Cronbach’s alphas ranging from .61 to .96 (Fernander et al, 2003; Jones et al, 2019; Volpe et al, 2020), which is in line with the current study (sample α = .76). The JHAC has been found to positively correlate with other active coping strategies and be discriminable from Type A behavioral patterns, anger and hostility, and emotion-focused and behavioral disengagement coping strategies (see Fernander et al, 2003).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Studies utilizing total scores on the JHAC scale have reported Cronbach’s alphas ranging from .61 to .96 (Fernander et al, 2003; Jones et al, 2019; Volpe et al, 2020), which is in line with the current study (sample α = .76). The JHAC has been found to positively correlate with other active coping strategies and be discriminable from Type A behavioral patterns, anger and hostility, and emotion-focused and behavioral disengagement coping strategies (see Fernander et al, 2003).…”
Section: Methodssupporting
confidence: 90%
“…Given the nonsignificance of John Henrysim in the context of self-esteem and maladaptive perfectionism, it is possible that this coping strategy is most relevant in the context of interpersonal stressors (e.g., racial discrimination) as opposed to internal stressors such as IP. Consistent with this assertion, our review of the scholarly literature found that the majority of John Henryism research work has examined this culturally relevant coping strategy in the context of interpersonal racerelated stressors, such as racial discrimination (Bennett et al, 2004;Jones et al, 2019;Volpe et al, 2020). Thus, while high effort coping may shape behavioral health outcomes in the face of race-related stressors, it may not influence perfectionistic tendencies or evaluations of one's own worth.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Racism has the ability to affect health via physical, psychological, social, functional, and spiritual domains. Specifically, racism-related stress has been related to hypertension ( Williams and Neighbors, 2001 , Anderson, 1989 ), cardiovascular issues ( Paradies et al, 2015 Sep 23 ), depression ( Willis et al, 2021 Aug 1 ), psychological distress ( Jackson et al, 1996 , Kelly et al, 2020 Apr ), and health behaviors such as eating disorders ( Glass et al, 2020 Nov ), substance abuse ( Jones et al, 2019 Jun , Desalu et al, 2019 Jun , Frazer et al, 2018 Feb ) and violence ( Sutton et al, 2020 Feb , Johnson et al, 2021 ). Additionally, racism-related stress has effects on social (ability to trust and interact with others) ( Hicken et al, 2013 Jun 1 , Odoms-Young, 2018 ), functional (academic and financial achievement) ( Grace and Nelson, 2019 Oct 2 , Butler-Barnes et al, 2018 Oct ) and spiritual (faith in higher powers) well-being ( Drolet and Lucas, 2020 Dec , Bailey et al, 2020 ).…”
Section: Minority Stress Theorymentioning
confidence: 99%
“…36,37 These high effort/active coping strategies may play an important role in influencing how stressful psychosocial experiences impact health outcomes, at times exacerbating negative health outcomes and at other times operating as a health protector. [36][37][38][39][40] Our findings suggest that among African Americans, HC is more closely associated with social support. These findings may indicate that while programs that target education as a means of increasing HC may have some efficacy among African Americans, utilizing approaches that incorporate or foster social support may produce a more meaningful impact on levels of HC among this subpopulation.…”
Section: Discussionmentioning
confidence: 59%